Melanophilin-induced primary cilia promote pancreatic cancer metastasis - Yu-Ying Chao; Ruei-Ci Lin; Ping-Jui Su; Chu-An Wang; Ting-Yuan Tu; Ya-Chin Hou; Yi-Tzui Tsai; I-Chen Peng; Shaw-Jenq Tsai; Yan-Shen Shan; Chia-Yih Wang (Cell Death and Disease)
Abstract Pancreatic ductal adenocarcinoma (PDAC) is one of the most malignant tumors because of its high metastatic ability. The glutamine (Gln)-deficient microenvironment contributes to PDAC metastasis; however, the underlying molecular mechanisms remain unclear. Here, we demonstrated that melanophilin (MLPH) promotes PDAC metastasis by inducing the regrowth of primary cilia. Using RNA sequencing, we found that MLPH was upregulated in Gln-deficient conditions. MLPH facilitated PDAC metastasis in vitro and in vivo. Clinically, high MLPH expression is positively correlated with metastasis and poor PDAC prognosis. MLPH localized to the centrosome and facilitated the regrowth of primary cilia. The primary ciliogenesis upregulated phospholipase C γ-1 (PLCG1) to promote PDAC metastasis. Interestingly, PLCG1 was localized to the primary cilia, and depletion of PLCG1 alleviated primary ciliogenesis, suggesting a feedforward role for PLCG1 in mediating primary ciliogenesis. Thus, our study revealed a novel function of the MLPH-primary cilia-PLCG1 axis in facilitating PDAC metastasis under Gln deficiency both in vitro and in vivo.